Phosphorus Availability Regulates TORC1 Signaling via LST8 in Chlamydomonas. Issue 1 (11th November 2019) - Couso, Inmaculada; Pérez-Pérez, María Esther; Ford, Megan M.; Martínez-Force, Enrique; Hicks, Leslie M.; Umen, James G.; Crespo, José L.
Abstract : Phosphorus regulates TORC1 signaling in the model green alga Chlamydomonas reinhardtii through the TOR-interacting protein LST8 and the global transcriptional regulator of phosphorus deficiency PSR1. Abstract: Target of rapamycin complex 1 (TORC1) is a central regulator of cell growth. It balances anabolic and catabolic processes in response to nutrients, growth factors, and energy availability. Nitrogen- and carbon-containing metabolites have been shown to activate TORC1 in yeast, animals, and plants. Here, we show that phosphorus (P) regulates TORC1 signaling in the model green alga Chlamydomonas ( Chlamydomonas reinhardtii ) via LST8, a conserved TORC1 subunit that interacts with the kinase domain of TOR. P starvation results in a sharp decrease in LST8 abundance and downregulation of TORC1 activity. A hypomorphic lst8 mutation resulted in decreased LST8 abundance, and it both reduced TORC1 signaling and altered the cellular response to P starvation. Additionally, we found that LST8 levels and TORC1 activity were not properly regulated in a mutant defective in the transcription factor PSR1, which is the major mediator of P deprivation responses in Chlamydomonas. Unlike wild-type cells, the psr1 mutant failed to downregulate LST8 abundance and TORC1 activity when under P limitation. These results identify PSR1 as an upstream regulator of TORC1 and demonstrate that TORC1 is a key component in P signaling in Chlamydomonas.